3rd International Conference on Radiation Safety & Security in Healthcare Services Proceedings of the Thirs, ICRSSHS, Dewan Budaya USM, Penang, Malaysia (Lecture Notes in Bioengineering, 2018)
This book presents the proceedings of the 3rd International Conference on Radiation Safety & Security in Healthcare Services. The conference was held at Universiti Sains Malaysia in Penang on 19th-20th August 2017.